2011
DOI: 10.1111/j.1476-5381.2011.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of P2X7 purinergic receptors in inflammatory and nociceptive changes accompanying cyclophosphamide‐induced haemorrhagic cystitis in mice

Abstract: BACKGROUND AND PURPOSEATP is released in response to cellular damage, and P2X7 receptors have an essential role in the onset and maintenance of pathological changes. Haemorrhagic cystitis (HC) is a well-known adverse effect of therapy with cyclophosphamide used for the treatment of many solid tumours and autoimmune conditions. Here we have evaluated the role of P2X7 receptors in a model of HC induced by cyclophosphamide. EXPERIMENTAL APPROACHEffects of pharmacological antagonism or genetic deletion of P2X7 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 61 publications
12
60
0
Order By: Relevance
“…administration of CPA at 400 mg/kg is in agreement with the previous evidence for macrophage accumulation in the bladder tissue after CPA at 300 mg/kg [13], and suggests the critical role of macrophages in the bladder pain, but not cystitis itself, in this animal model. It is also consistent with our recent report indicating that the CPA-induced bladder pain, but not cystitis itself, involves the activation of RAGE by endogenous high mobility group box 1 [11], one of damage-associated molecular patterns, which can be secreted by activated macrophages [14].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…administration of CPA at 400 mg/kg is in agreement with the previous evidence for macrophage accumulation in the bladder tissue after CPA at 300 mg/kg [13], and suggests the critical role of macrophages in the bladder pain, but not cystitis itself, in this animal model. It is also consistent with our recent report indicating that the CPA-induced bladder pain, but not cystitis itself, involves the activation of RAGE by endogenous high mobility group box 1 [11], one of damage-associated molecular patterns, which can be secreted by activated macrophages [14].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, it is noteworthy that the CPA-induced bladder pain, but not bladder swelling, was prevented by macrophage depletion with liposomal clodronate in our ongoing study (data not shown). The mechanisms by which CPA treatment activates macrophages remain unknown, whereas there is evidence that endogenous ATP released from the urothelial cells might contribute to macrophage infiltration in the bladder tissue [13]. Considering the decrease in LPS-induced cytokine production by peritoneal macrophages from RC-stressed mice, RC stress appears to reduce the macrophage activity, leading to the decreased bladder pain/referred hyperalgesia in response to CPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research suggested that the expression of P2X4 receptor in the dorsal horn of the thoracic cord increased in the visceral pain model [23] and that the expressions of P2X7 receptors were increased in the jejunum of postinflammatory visceral hypersensitivity mice [24] and haemorrhagic cystitis mice model [25], respectively. Our results showed that except the P2X2 and P2X3 receptors, the expressions of P2X4 and P2X7 receptors increased obviously in visceral pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of these studies also had supporting P2X7 KO mouse data alongside P2X7 antagonist data, further implicating P2X7 in a number of disease processes. These include models of hemorrhagic cystitis (Martins et al, 2012), glomerulonephritis (Taylor et al, 2009b), hypertension and renal injury , lung inflammation (Lucattelli et al, 2011), allergic airway inflammation , pancreatitis (Hoque et al, 2011), and graft-versus-host disease (Wilhelm et al, 2010).…”
Section: E P2x7 Antagonists In Rodent Models Of Disorders Associatedmentioning
confidence: 99%